Correlations between moral courage, moral sensitivity, and ethical decision-making by nurse interns: a cross-sectional study - Zongting Luo; Lan Tao; Carol Chunfeng Wang; Nan Zheng; Xiaolin Ma; Yi Quan; Jian Zhou; Zhen Zeng; Lijuan Chen; Yue Chang (BMC Nursing, 2023)
Abstract Background Clinical decision-making involves ethical issues that become more and more complex. Nurse interns must be more skilled in making rational and timely decisions when facing ethical dilemmas. The contributing factors and their relationships that challenge ethical decision-making among nurse interns must be fully understood, as this level of knowledge can support the development of strategies and interventions that improve the ethical decision-making ability of nurse interns. Objective This study examined the relationships between moral courage, moral sensitivity, and ethical decision-making by nurse interns. In addition, we investigated whether moral sensitivity mediates the relationship between moral courage and ethical decision-making. Design A descriptive cross-sectional study using an online questionnaire. Setting The study sampled nurse interns from Class iii Grade A general hospitals in Sichuan Province, China. Participants A convenience sampling method was used to select 1334 nurse interns from March 2022 to May 2022. Methods A general information questionnaire, the Nurses’ Moral Courage Scale (NMCS), the Chinese Moral Sensitivity Questionnaire (MSQ), and the Judgement About Nursing Decision (JAND) were used for data collection. Data was processed and analysed using SPSS 26.0 and Amos 28.0. Data analysis included descriptive statistics, Pearson correlation analysis, and structural equation modelling. Results Moral courage was found to be positively correlated with ethical decision-making (P < 0.01). Moral sensitivity was also positively correlated with ethical decision-making (P < 0.01) and had a mediating effect on the relationship between moral courage and ethical decision-making (P < 0.01). Conclusions The moral courage and moral sensitivity of nurse interns are positively correlated with ethical decision-making ability. Moral sensitivity significantly mediates the relationship between moral courage and ethical decision-making ability. The knowledge gained from this study can inform educational strategies and interventions in supporting the development of nurse interns’ ethical decision-making ability.